2005
DOI: 10.1113/jphysiol.2005.088229
|View full text |Cite
|
Sign up to set email alerts
|

Hemicerebellectomy blocks the enhancement of cortical motor output associated with repetitive somatosensory stimulation in the rat

Abstract: Repetitive peripheral stimulation is associated with an enhancement of the intensity of corticomotor responses. We analysed the effects of hemicerebellectomy on the modulation of cortical motor output associated with repetitive electrical stimulation of the sciatic nerve in the rat. Hemicerebellectomy blocked the enhancement of the corticomotor response. The cerebellum is a key player in this form of short-term plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…It has been shown that peripheral electrical somatosensory stimulation increases contralateral M1 excitability reflected in increased MEP amplitudes in healthy humans and animals [190, 191]. In rodents, this effect is blocked by cerebellar lesions [191193] indicating that the cerebellum facilitates this type of plasticity.…”
Section: The Cerebellum and Control Of Corticomotor Excitability (Abmentioning
confidence: 99%
“…It has been shown that peripheral electrical somatosensory stimulation increases contralateral M1 excitability reflected in increased MEP amplitudes in healthy humans and animals [190, 191]. In rodents, this effect is blocked by cerebellar lesions [191193] indicating that the cerebellum facilitates this type of plasticity.…”
Section: The Cerebellum and Control Of Corticomotor Excitability (Abmentioning
confidence: 99%
“…Experimentally, potentiation of the corticomotor response is induced by preceding trains of repetitive stimuli applied to a peripheral nerve [25, 26]. The cerebellum is involved in this potentiation since removal of the cerebellar hemisphere impairs this short-term potentiation [27]. In addition to MEPs, the effects of the cerebellar hemisphere on contralateral motor cortex can be examined using a protocol of cerebellocortical inhibition (CCI).…”
Section: Evidence Suggesting Pathogenesis Of Gad65 In Developmentmentioning
confidence: 99%
“…That is, MEPs decrease in magnitude when stimulation of a cerebellar hemisphere is applied 2.1 msec before stimulation of the contralateral motor cortex [26]. Mechanistically, stimulation of the inhibitory cerebellar PCs inhibits motor cortex activity through the deep cerebellar nuclei-thalamus-motor cortex pathway (see diagram in Figure 1(a)) [2327]. The inhibition of cerebellar cortex upon cerebellar nuclei is a key mechanism of cerebellar circuitry [2327].…”
Section: Evidence Suggesting Pathogenesis Of Gad65 In Developmentmentioning
confidence: 99%
“…In monkeys, microstimulation of deep cerebellar nuclei often increases the likelihood of discharge of contralateral M1 neurons [2]. In rats, hemicerebellectomy decreases ICF [21] and blocks facilitatory effects of somatosensory stimulation on M1 excitability [22]. The latter phenomenon is also observed after inhibition of the interpositus nucleus [23, 24].…”
Section: Discussionmentioning
confidence: 99%